2019
DOI: 10.1186/s13578-019-0344-5
|View full text |Cite
|
Sign up to set email alerts
|

KIF5B modulates central spindle organization in late-stage cytokinesis in chondrocytes

Abstract: Background The growth plate is a special region of the cartilage that drives longitudinal growth of long bones. Proliferating chondrocytes in the growth plate, arranged in columns, divide perpendicular to the long axis of the growth plate then intercalate to re-align with parental columns. Which molecular partners maintain growth plate columnar structures and chondrocyte cytokinesis has not been fully revealed. It is reported that kinesin family member 3A (KIF3A), a subunit of kinesin-2, plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 44 publications
(71 reference statements)
3
16
0
Order By: Relevance
“…Two animal model experiments showed that loss of function of KIF5B can cause kyphomelic dysplasia. First, chondrocyte‐specific knockout of Kif5b in mice was shown to produce a disorganized growth plate, leading to bone deformity 16 . Second, double mutants disrupting the two zebrafish kif5b caused abnormal skeletal morphogenesis and the curvature of Meckel's and ceratohyal cartilages 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Two animal model experiments showed that loss of function of KIF5B can cause kyphomelic dysplasia. First, chondrocyte‐specific knockout of Kif5b in mice was shown to produce a disorganized growth plate, leading to bone deformity 16 . Second, double mutants disrupting the two zebrafish kif5b caused abnormal skeletal morphogenesis and the curvature of Meckel's and ceratohyal cartilages 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations could cause reduced proliferation of growth plate chondrocytes, which in turn could limit bone growth. Disrupting cytokinesis in the growth plate causes shorter bones and stature in mice ( Gan et al, 2019 ), and mutations in KIF22 could affect development via this mechanism. The presence of pathologies in other cartilaginous tissues, including the larynx and trachea, in patients with mutations in the motor domain of KIF22 ( Boyden et al, 2011 ) is also consistent with a disease etiology based in aberrant chondrocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to KIF3A and KIF7, deletion of KIF5B in chondrocytes impairs chondrocyte proliferation and differentiation. Notably, loss of KIF5B in chondrocytes leads to delayed and defective cytokinesis, which thereby causes incomplete cell rotation, disrupts proliferation and differentiation, and results in a disorganized growth plate (Gan et al 2019). These findings demonstrate that KIF5B is a key modulator of cytokinesis in chondrocytes via maintenance of central spindle organization.…”
Section: Primary Cilia Regulate Cartilage Formationmentioning
confidence: 84%
“…These findings demonstrate that KIF5B is a key modulator of cytokinesis in chondrocytes via maintenance of central spindle organization. KIF3B and KIF4 have been found to participate in cytokinesis and central spindle assembly (Gan et al 2019). Whether other KIF proteins or IFT proteins also play role(s) in regulating cytokinesis needs to be further studied.…”
Section: Primary Cilia Regulate Cartilage Formationmentioning
confidence: 99%